Bugs in the system: the logic of insect farming research is flawed by unfounded assumptions - Corentin Biteau; Tom Bry-Chevalier; Dustin Crummett; Ren Ryba; Michael St. Jules (npj Sustainable Agriculture)
Abstract Insect farming is frequently proposed as an emerging industry that can improve the environmental and economic sustainability of the food system. However, existing research often overlooks significant challenges. In this article, we identify three bugs in the scientific literature on insect farming: (1) the overreliance on a handful of old studies when discussing environmental impacts; (2) the pervasive assumption that insect farms will utilise food waste; and (3) the reliance on theoretical price projections that do not hold up under commercial conditions. We then discuss how promising technologies, despite their theoretical benefits, often encounter social and material challenges in practice. Debugging the literature will involve producing more realistic life-cycle assessments, which will provide policymakers and industry with the data needed to make informed decisions for a truly sustainable food system.